2018
DOI: 10.1093/nar/gky748
|View full text |Cite
|
Sign up to set email alerts
|

The ATPase activity of E. coli RecA prevents accumulation of toxic complexes formed by erroneous binding to undamaged double stranded DNA

Abstract: The Escherichia coli RecA protein catalyzes the central step of homologous recombination using its homology search and strand exchange activity. RecA is a DNA-dependent ATPase, but its homology search and strand exchange activities are largely independent of its ATPase activity. ATP hydrolysis converts a high affinity DNA binding form, RecA-ATP, to a low affinity form RecA-ADP, thereby supporting an ATP hydrolysis-dependent dynamic cycle of DNA binding and dissociation. We provide evidence for a novel function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Because the Dmc1-E157D mutant is modeled after RecA-E96D, which has been shown to form foci on undamaged DNA, we wanted to ask whether the same was true of the corresponding Dmc1 mutant [35]. To determine whether any of the foci that we observed in the dmc1-E157D background resulted from binding to chromosomes independent of DSBs, we introduced the spo11 mutation into our dmc1-E157D strains to block DSB formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Dmc1-E157D mutant is modeled after RecA-E96D, which has been shown to form foci on undamaged DNA, we wanted to ask whether the same was true of the corresponding Dmc1 mutant [35]. To determine whether any of the foci that we observed in the dmc1-E157D background resulted from binding to chromosomes independent of DSBs, we introduced the spo11 mutation into our dmc1-E157D strains to block DSB formation.…”
Section: Resultsmentioning
confidence: 99%
“…Under normal circumstances in vivo , RecA family proteins form nucleoprotein filaments that are shorter than the resolution limit of conventional light microscopy (~200 nanometers). This is true for RecA, and for both eukaryotic RecA homologs, Rad51 and Dmc1 [3235]. Super-resolution microscopy imaging of Dmc1 filaments formed during meiosis indicates that Dmc1 filaments are typically about 120 nanometers (nm) long, a length that corresponds to roughly 100 nucleotides when taking into account the fact that RecA family proteins stretch the DNA ~1.5 fold when assembled into a filament [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between RecA's ATPase activity and its DNA-binding affinity, together with the demonstration that strand exchange can occur in the absence of ATP hydrolysis, led to the proposal that a function of RecA's ATPase activity is to release the protein from the products of strand exchange, thereby making the hybrid intermediate available to late-acting recombination proteins. With this view, the critical role of RecA's ATPase activity is to prevent accumulation of toxic dsDNA complexes caused by direct binding of RecA to undamaged regions of dsDNA (Gataulin et al, 2018). Here, we have an ATP hydrolysis-dependent error-correction function that allows cells to discard the dead-end and potentially toxic complexes that result from direct RecA binding to dsDNA.…”
Section: Other Processes Working Out Specific Features Of Nucleic Acidsmentioning
confidence: 99%
“…Additionally, ATP hydrolysis promotes the disassembly of RecA-DNA filaments after completion of strand exchange (68). Furthermore, nucleoid surface spreading, immunostaining and super resolution microscopy studies performed on ATPase-defective mutants RecAK250N and RecAE96D in vivo revealed that ATP hydrolysis also promotes disassembly from undamaged regions of dsDNA, preventing the accumulation of dead-end and potentially toxic complexes (69).…”
Section: Formation Of the Postsynaptic Filament And Strand Exchangementioning
confidence: 99%